2020
DOI: 10.3892/etm.2020.9370
|View full text |Cite
|
Sign up to set email alerts
|

Paroxetine combined with fluorouracil plays a therapeutic role in mouse models of colorectal cancer with depression through inhibiting IL‑22 expression to regulate the MAPK signaling pathway

Abstract: The objective of the present study was to observe the therapeutic effect of paroxetine combined with fluorouracil on mice with colorectal cancer (CRC) complicated with depression and to explore its mechanism of action. Using chronic mild stress and xenograft tumor methods to model CRC complicated with depression, 60 BALB/c mice were randomly divided into control, tumor model, tumor depression model, tumor depression antidepressant, tumor depression chemotherapy and tumor depression antidepressant plus chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…As IL-22 is involved in the induction of inflammatory responses in other tissues, we investigated its effects on the production of inflammatory cytokines [ 41 , 51 ], and found that treatment of BV2 and HT22 cells with IL-22 increased the levels of TNF-α ( Figure 2 A) and IL-6 ( Figure S1 ). Previous studies have shown that binding of IL-22 to IL-22Rα induces the JAK1, STAT3, and STAT5 pathways, as well as the MAP kinase pathways [ 17 , 52 , 53 ]. In line with these reports, we found that pretreatment of BV2 cells with SP600125 (a specific inhibitor of JNK) and pretreatment of HT22 cells with S3I-201 (a specific inhibitor of STAT3) attenuated the IL-22-induced increase in TNF-α ( Figure 3 A,B).…”
Section: Discussionmentioning
confidence: 99%
“…As IL-22 is involved in the induction of inflammatory responses in other tissues, we investigated its effects on the production of inflammatory cytokines [ 41 , 51 ], and found that treatment of BV2 and HT22 cells with IL-22 increased the levels of TNF-α ( Figure 2 A) and IL-6 ( Figure S1 ). Previous studies have shown that binding of IL-22 to IL-22Rα induces the JAK1, STAT3, and STAT5 pathways, as well as the MAP kinase pathways [ 17 , 52 , 53 ]. In line with these reports, we found that pretreatment of BV2 cells with SP600125 (a specific inhibitor of JNK) and pretreatment of HT22 cells with S3I-201 (a specific inhibitor of STAT3) attenuated the IL-22-induced increase in TNF-α ( Figure 3 A,B).…”
Section: Discussionmentioning
confidence: 99%
“…Regulating the CUMS-induced MAPK pathway and NF-κB protein complex activation can alleviate depression-like behavior in mice (Su et al 2017 ). Paroxetine combined with fluorouracil, ketamine and ghrelin and other drugs can show antidepressant-like effects via the MAPK signaling pathway (Zhang et al 2020 ; Humo et al 2020 ; Han et al 2019 ). Cui et al found that HL can alleviate inflammation by regulating the expression of pro-inflammatory cytokines through MAPK signaling pathway, thereby inhibiting the occurrence and development of IR and diabetes (Cui et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regulating the CUMS-induced MAPK pathway and NF-κB protein complex activation can alleviate depression-like behavior in mice [108]. Paroxetine combined with uorouracil, ketamine and ghrelin and other drugs can show antidepressant-like effects via the MAPK signaling pathway [109][110][111]. In addition, resveratrol can attenuate cardiac dysfunction caused by diabetes, and the effects are related to down-regulation of AT1R-ERK/p38 MAPK signaling pathway [112].…”
Section: Discussionmentioning
confidence: 99%